KOMPARASI TRANSFORMASI MANAJEMEN DALAM IMPLEMENTASI INOVASI PENDIDIKAN DIGITAL - Agriyosda Syeftia; Hesti Wihandini; Neneng Puri Rachmawati; Waska Warta (Jurnal Manajemen Pendidikan, 2026)
Objective: This study examines educational management transformation in implementing digital education innovation at SMP Mutiara Bunda Bandung City and SMP Telkom Bandung Regency using the Technology–Organization–Environment (TOE) Framework to identify how technological, organizational, and environmental factors influence digital transformation. Methods: This qualitative study employed a multiple case study design. Data were collected through in-depth interviews, participatory observations, focus group discussions, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, conclusion drawing, and cross-case analysis. Results: The findings indicate that SMP Telkom demonstrates stronger digital system integration, technology standardization, and structured digital leadership, while SMP Mutiara Bunda emphasizes organizational flexibility through participatory leadership and an adaptive digital culture. Environmental support and institutional characteristics significantly influence each school's transformation strategy. Novelty: This study extends the TOE Framework by proposing a TOE-Based Educational Digital Management Transformation Model comprising four stages: digital awareness, digital adaptation, digital integration, and digital innovation and sustainability, highlighting that successful digital innovation depends on integrated management transformation rather than technology adoption alone.